(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The contemporary world is characterized by the large amount of information released on the world wide web and the consequent ways of using this data. As a result, important legal barriers to personality rights arise, in particular privacy regarding misuse or unauthorized use of such data. The purpose of this paper is to discuss the context of the exposure of children’s personal data when parents, family members, friends or anyone related to minors, who enter information about them on the Internet, called shareting as opposed to freedom of expression. To this end, the practice will be analyzed through the mechanisms of the Internet Civil Framework (MCI), the General Personal Data Protection Act (LGPD) and case law to address such a collision of rules. The article also examines the role of application providers, particularly social networks and search engines, in creating mechanisms that ensure children’s right to forget and prevent excessive information sharing by parents; In this regard, a comparison of the Brazilian and European models was performed. Finally, within the normative scenario, it is concluded that the LGPD sought to impose limits on the treatment of children’s data, a measure that conveys the most advanced in terms of strengthening children and adolescents as subjects of rights and protagonists of their children rights.